2023
DOI: 10.1093/braincomms/fcad122
|View full text |Cite
|
Sign up to set email alerts
|

Neural dysregulation in post-COVID fatigue

Abstract: Following infection from SARS-CoV-2, a substantial minority of people develop lingering after-effects known as ‘long COVID’. Fatigue is a common complaint with substantial impact on daily life, but the neural mechanisms behind post-COVID fatigue remain unclear. We recruited 37 volunteers with self-reported fatigue after a mild COVID infection and carried out a battery of behavioural and neurophysiological tests assessing the central, peripheral and autonomic nervous systems. In co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In a previous study 12 in long COVID after non-severe SARS-CoV-2 infection, where there had been no requirement for acute hospital in-patient care, we demonstrated changes in muscle physiology. In addition, we found reduced responsiveness in some of the neural circuitry governing cortical excitability, and a rise in the resting heart rate probably indicating an altered balance between sympathetic and parasympathetic systems.…”
Section: Introductionsupporting
confidence: 52%
“…In a previous study 12 in long COVID after non-severe SARS-CoV-2 infection, where there had been no requirement for acute hospital in-patient care, we demonstrated changes in muscle physiology. In addition, we found reduced responsiveness in some of the neural circuitry governing cortical excitability, and a rise in the resting heart rate probably indicating an altered balance between sympathetic and parasympathetic systems.…”
Section: Introductionsupporting
confidence: 52%
“…In our previous study 13 , we provided evidence that measures of the central (intracortical facilitation, TMS_ICF), peripheral (peripheral fatigue, TI_PeriphFatigue) and autonomic (mean heart rate, Mean_HR and peripheral oxygen saturation, SaO2) nervous systems were different between people with pCF compared to sex-and age-matched controls. However, these findings could not infer causation; measures could have been different prior to the infection (and thus conferred an increased likelihood of developing pCF) or the abnormal measures could be a consequence of the infection (and hence might be useful as a biomarker for tracking changes in fatigue).…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study 13 we demonstrated changes in muscle physiology in long COVID after non-severe SARS-CoV-2 infection, where there had been no requirement for acute hospital in-patient care. These changes might explain some of the symptoms of fatigue described by patients.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations